"You're my bitch": women's experiences of gender-based cyber- harassment on the internet in South Africa, flaming and trolling - Van Den Heever, Savannah (Department of Public Law, 2025)
This research paper examines how women experience gender-based cyber-harassment in South Africa. It focuses on two forms of cyber-harassment: flaming and trolling. It further discusses how women change their online and offline behaviours due to their experiences and what they recommend to other women and social networking sites to manage and combat it. Using individual interviews and following a standardised questionnaire, nine women were interviewed, and their responses were thematically analysed to better learn and understand their lived experiences. As a result, this research demonstrates that cyber-harassment has detrimental effects on women's psychological states and behaviours. It argues that cyber-harassment mirrors traditional gender-based violence in its causes and manifestations and that women have valid recommendations about how to manage cyber-harassment. Such recommendations are aimed towards social networking sites and other women who navigate them. It emphasises that even with these recommendations, women are left disillusioned at the lack of support for gender-based cyber-harassment, just as they are for traditional gender- based violence.